Pelatihan Pijat Oksitosin kepada Keluarga untuk Meningkatkan Produksi ASI pada Ibu Menyusui - Asmin, Risna Yunita; Rahmat, Rezqiqah Aulia; Pratiwi, Desi Eka (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Breast milk production is significantly influenced by hormonal and psychological factors, one of which is stimulation of the hormone oxytocin. Oxytocin massage is a simple technique that can be performed by family members to stimulate breast milk production. This community service program aims to provide oxytocin massage training to families of breastfeeding mothers as a promotional intervention to increase breast milk production. The activity was implemented through counseling, demonstrations, hands-on practice, and follow-up mentoring for 25 families in Sukamaju Village. Evaluation results showed an increase in family knowledge and skills in performing oxytocin massage, as well as a positive impact on breast milk flow. This training has proven effective and can be recommended as a routine program in pregnancy and breastfeeding classes at the community level.